Soseki natsume kokoro - Natsume, Soseki (Tuttle Publishing, 2025)
""Natsume Soseki is the representative modern Japanese novelist, a figure of truly national stature." -Haruki Murakami A chance encounter irrevocably links a university student to an older man he simply calls Sensei ("Teacher"). Intrigued by Sensei's aloofness, the student visits him with increasing frequency, and Sensei and his beautiful wife eventually open their home and lives to him. The student graduates and is called home to care for his dying father, but Sensei draws him back with a letter revealing a secret that has shadowed him since youth. Written in 1914, toward the end of Soseki's career, Kokoro provides a timeless psychological analysis of man's alienation from society. It is recognized as one of his most important works and a milestone in the emergence of the psychological novel in Japan. Its universal themes of friendship, betrayal and the struggle for meaning in a rapidly changing world continue to resonate today"--